Cost-effectiveness of rivaroxaban versus warfarin for treatment of nonvalvular atrial fibrillation in patients with worsening renal function. (1st May 2019) - Salcedo, Jonathan; Hay, Joel W.; Lam, Jenny
Abstract: Background: Nonvalvular atrial fibrillation (NVAF) is highly prevalent and increases the risks of cardiovascular events. In a recent subgroup analysis, treatment response was shown to vary for patients exhibiting worsening renal function (WRF) on-treatment. It is important to understand the cost-effectiveness of novel oral anticoagulant (NOAC) use in this population. Methods: A cost-effectiveness analysis (CEA) was conducted using a Markov model to determine whether NOAC rivaroxaban treatment is cost-effective relative to warfarin in NVAF patients with on-treatment WRF. Input parameters were sourced from clinical literature including a multicenter clinical trial and subgroup analysis. We studied elderly US male patients at increased risk for stroke (CHADS2 score ≥ 2) undergoing treatment for NVAF and exhibiting WRF. Main outcome measures included total healthcare costs in 2017 US dollars (societal perspective), total quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER), and incremental net monetary benefits (INMB) per-patient. Results: The remaining lifetime use of rivaroxaban is associated with 5.69 QALYs at a cost of 66, 075 per patient, while warfarin produced 5.22 QALYs with costs of 78, 504 per patient. At a willingness-to-pay (WTP) of 150, 000 per QALY, incremental net monetary benefits (INMB) per patient are 83, 590. In our population, treatment with warfarin was dominated by rivaroxaban in 99.4% of 10, 000 simulations. Conclusions: Rivaroxaban is likely a dominant treatment over warfarin in elderly US male NVAF patients exhibiting WRF, providing increased QALYs at a decreased overall cost. Application of these findings may require healthcare providers to predict which patients are likely to exhibit WRF. Highlights: Rivaroxaban is dominant to warfarin for NVAF with WRF in elderly US males. At 150, 000 per year of perfect health, monetary benefits are 83, 590 per patient. Rivaroxaban provides greater benefit at a lower cost than warfarin. Rivaroxaban may be an attractive alternative to warfarin in this population.